Discourse on Forgiveness and Punishment in the Colombian Civil-War 1859-1862 (2008)
This article shows the crossroads of the war discourse with, peace, forgiveness and punishment, and revenge and clemency in the context of the Colombian civil war between 1859 and 1862. It attempts to emphasize that what distinguished the peace strategy,